Геоінформаційна екологічна модель сучасного стану поверхневих вод р. Сіверський Донець - Жирнов, П.В. (Геоінформатика, 2015)
Проаналізовано гідроекологічний стан поверхневих вод р. Сіверський Донець у межах двох транскордонних областей України – Харківської та Луганської. Виділено типи техногенних систем, які впливають на екологічний стан поверхневих вод. Побудовано геоінформаційну модель цього стану. Здійснено районування прибережних територій за критерієм гостроти гідроекологічної ситуації. Дан анализ гидроэкологического состояния поверхностных вод р. Северский Донец в пределах двух трансграничных областей Украины – Харьковской и Луганской. Выделены типы техногенных систем, влияющих на экологическое состояние поверхностных вод. Построена геоинформационная модель этого состояния. Осуществлено районирование прибрежных территорий по критерию остроты гидроэкологической ситуации. Purpose. The purpose of the article is to describe environmental GIS model of the surface water of the Seversky Donets River within two cross-border regions of Kharkiv (the river originates in Belgorod region, Russia) and Luhansk (it flows into the Don River, Rostov region, Russia); to identify technological system types affecting the ecological status of surface waters; to conduct the Seversky Donets coastal areas zoning on the basis of the gravity of the environmental situation; to create percentage polluting components cartograms using software ArcGIS ArcMap 10.
Design/methodology/approach. To determine the pollution degree of the Seversky Donets surface waters we applied mathematical and hydrochemical methods. Statistical method were also widely used. To create polluting components cartograms we applied geoinformation modeling, which are well descripted in scientific works of V.K. Shitikova, G.S. Rosenberg and T.D. Zinchenko.
Findings. Analyzing the status of surface waters in the floodplain of the Seversky Donets River on the border line of Kharkov and Luhansk regions, we can argue that the hydroecological situation is catastrophic due to strong anthropogenic pressure in the last administrative subdivision. Unlike the results of the hydrochemical analysis of water samples from Kharkiv region, in the water area of Luhansk region such dangerous substances and compounds as phenols, mercury, aniline, vanadium, bismuth, tin, lead, antimony, cadmium, molybdenum, arsenic, fluoride, formaldehyde, cyanide and thiocyanate were found. In Kharkiv region, only a conflict and stress state of the hydroecosystem was detected, when due to environmental protection, the state of surface water may return to satisfactory category. In Luhansk region, however, these changes are irreversible: only areas of a critical and catastrophic level of hydroecological situation were found there.
Practical value/implications. Results of the article have practical importance for improving the management of the water sector in Kharkiv and Luhansk regions, through creating a system of regional hydroecological monitoring of water objects and justification of measures for water resources protection. The author uses the obtained results in the research project “Cross-boundary cooperation in «Slabozhaschina» and «Yaroslavovna» regions” (Scientific and research urban planning institute, 2013). The methodology applied by the author to create hydroecological model of the Seversky Donets River can be used for the environmental assessment of other water objects in Ukraine.